Pharmacokinetic Evaluation of Two Doses of Aminophylline/Theophylline Administered as Multiple Intermittent Infusions to Iranian Apneic Premature Neonates: Pharmacokinetic of multiple intermittent infusions aminophylline/theophylline - Afsaneh Vazin; Mohammad Moslehi; Mehrdad hamidi; Narjes Pishva (Iranian Journal of Pharmaceutical Sciences, 2011)
Many premature neonates suffer from apnea, and aminophylline is administrated for them. The objective of this study was to reveal pharmacokinetic (PK) parameters of theophylline in Iranian premature neonates. Premature neonates (68) who were admitted in the Neonatal Intensive Care Unit (NICU) of Namazi, Hafez, and Zeinabieh Hospitals were included in the study. All of them received 5 mg/kg aminophylline. One group received 1 mg/kg/8 h and the other group received 2 mg/kg/8 h as maintenance dose. One blood sample was taken in steady-state on just before eleventh dose. Theophylline level was determined with immunoassay kit. There was a significant difference in average serum concentration (Cave ss ) between two dosing levels (7.69±2.92 µg/ml vs. 11.44±3.80 µg/ml). Furthermore, the total clearance and volume of distribution were significantly different in two groups. No significant correlation could be found between the gender and Cave ss in different dosing levels. Postnatal age and postconceptional age have significant relationship with Cave ss just in the second group. According to theophylline serum concentrations, these two dosages produce therapeutically safe and effective blood levels. Pharmacokinetic parameters in these patients–in two dosing groups–approximately are correlated with other reported and recommended amounts.